FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN MEMBACA LABEL KEMASAN PANGAN PADA MAHASISWA FKM USU MEDAN 2015 - Alvira Fransiska Ginting; Evawany Y Aritonang; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food label is any information about the food in the form of images, text, a combination of both, or other forms that are included in the packaging of food. The role of the labels on food products is vital in prouding educational advice for the community and into value added products. The labels will did consumers in selecting food products is needed. The study aims to determine the factors associated with the habit of reading food labels on students FKM USU Medan 2015. This research is an deskriptif using cross sectional design. This study population are reguler students S1 FKM USU 2012-2014. Samples were taken using the method of proportional strata totaling 92 people. Primary data was collected through interviews using a questionnaire with accidental sampling method and presented in the form of a frequency distribution table. The results showed that 68,5% of the students good knowledge, 55,4% had a moderate perception on food packaging labels, and 47,8% of students have a habit of being in reading food labels. Significantly, there is no relationship between the sexes with the habit of reading food labels (p = 0,223), there was no association with knowledge of the habit of reading the package of food labels label of food packaging (p = 0,195) and there is a correlation between the perception of the habit of reading the food label to label food packaging (p = 0,002). To the goverment in order to improve the dissemination label food packaging as well as provide insight into the importance of reading to the community about the benefits of reading the information on label of food packaging. Keywords: Label reading habits, gender, knowledge, perception